The determinants of risk culture in banking sectors: Malaysian case - Rozila, Hamzah (2014)
Risk culture has become a significant aspect of the organization, especially in financial institutions. It has become one of the critical factors of a successful risk management practice. A strong risk culture needs to be developed at all levels of the organization. However, there is still a lack of evidence of risk culture, especially in the banking sector. Thus, the aim of this study is to examine the determinant factors of risk culture in Malaysia banking sector. The study used survey as the research methodology. The questionnaire was distributed to all levels of bank staffs. The stepwise multiple regression was used to test the relationship between determinant factors and risk culture. Risk culture was found to be influenced by the length of services among bank staffs, employee roles and policy and guidelines. While the top management roles were insignificant towards risk culture. The result indicated that employee roles and policy and guidelines are important to develop a strong risk culture in the banking sector. It can create awareness among bank staff the importance of their roles towards risk culture. The results also provide useful inputs in guiding the bank regulators to evaluate existing policies and guidelines on creating an effective risk culture in the banking sector.